Atrial Cardiomyopathy: An Emerging Cause of the Embolic Stroke of Undetermined Source - Ning, Yuye; Tse, Gary; Luo, Guogang; Li, Guoliang (Frontiers in Cardiovascular Medicine, 2021)
Nearly 30% of ischemic strokes have an unknown cause, and is referred to as cryptogenic strokes (CS). Imaging studies suggest a large proportion of these patients show features that are consistent with embolism, and thus the term embolic stroke of undetermined source (ESUS) was proposed to describe these CS patients. Atrial cardiomyopathy predisposes to thrombus formation and thus embolic stroke even in the absence of atrial fibrillation (AF). This may provide a mechanistic link with ESUS, suggesting that anticoagulant therapy may be more beneficial than antiplatelet therapy in ESUS patients with atrial cardiomyopathy. The present review discusses the concept of atrial cardiomyopathy and ESUS, the relationship between them based on the mechanisms and clinical evidences, suggests that atrial cardiomyopathy may be a potential mechanism of ESUS, and highlights theoretical basis that supports anticoagulant therapy may be more applicable to ESUS patients with atrial cardiomyopathy, aims to help us to better understand and identify the risk of ESUS, thereby improving the management of these patients in clinical practice.